Comparison of the efficacies of normal saline versus hypertonic saline in the management of acute bronchiolitis’ - Koker, Oya; Ozdogan, Sebnem; Kose, Gulsen; Yildirmak, Zeynep Y. (International Journal of Contemporary Pediatrics, 2016)
Background: The aim of this study was to compare the efficacies of saline solutions of different concentrations used for the management of infants with mild to moderate bronchiolitis. Methods: A retrospective chart review of 46 children, aged 1-24 months, diagnosed with acute bronchiolitis was performed. The patients were separated into 2 groups: normal saline and 3% hypertonic saline. Length of hospital stay, modified respiratory assessment score (MRAS) at admission, at 48 hours of admission and at discharge were compared. Results: MRAS evaluated at admission, at 48 hours after admission and at discharge and length of hospital stay did not reveal significant difference between the two groups (p>0.05). Conclusions: Comparison of two different treatments, salbutamol applied in combination with either normal saline or 3% hypertonic saline, did not reveal any statistically significant differences with respect to symptomatic improvement or length of hospital stay.